Monitoring Indonesia’s Energy Mix Achievement Using Simple Linear Regression - Raharjo, Jangkung; Rahmat, Basuki; Hasudungan, Jaspar (International Journal of Energy Economics and Policy, 2022)
The energy crisis has become a global issue. It can be seen in various countries worldwide experiencing an energy crisis. The energy crisis and global warming encourage countries to use renewable energy sources significantly from time to time. Based on historical data of installed capacity, it can be calculated the installed capacity in 2025 using a simple linear regression method. Renewable energy generating capacity is obtained from this installed capacity, meeting 23% of the total. The results of a simple linear regression show that in 2025, the installed capacity of renewable energy plants is 22.66%. It means that there is a deviation of 0.34% from the target. Meanwhile, for 2050, the achievement of the energy mix is 28.47%, which means that it is 2.53% lower than the target of 31%. Conformity between the general national energy plan and the regional one is essential.